Syllinae (Syllidae: polychaeta) from the Mediterranean coast of Egypt with the description of two new species - ABD-ELNABY, F.A.; MARTIN, G.S. (Mediterranean Marine Science, 2011)
This is the second paper dealing with the Syllidae collected on soft and hard bottom from the north-western coast of Egypt (Mediterranean Sea) and southern part of the Suez Canal. Eleven species were reported, two of them seem to be new to science, (Syllis sp.1 and Syllissp.2), but need further examination. Six species namely Opisthosyllis brunnea, Syllis columbretensis, Syllis gerlachi, Syllis ergeni, Syllis pulvinata andTrypanosyllis coeliaca were recorded as new for Egyptian waters.